Financial Performance Assessment of PT. Angkasa Pura II in Comparison with other Airport Companies Locally and Globally - Agustina, Meidita; Soekarno, Subiakto (Journal of Business and Management, 2012)
In relation to the magnitude of migration on population growth is causing many residents Indonesia, especially Jakarta, who was traveling out of town after another. It cause the number of users of transportation between the city / country is becoming increasingly high, especially aircraft.PT Angkasa Pura II is a monopolistic market, where they have no competitor in its country. Growth in passenger numbers continued to move up to 18.5% since 2010. Development of airport development depends on economic growth in the country. In accordance with the type of market is monopolistic market segments, the airport is quite focused on the stability of their internal performance.This final project presents the reader about how important analyzing the performance assessment in order to reach the best performance. The final project will talk about the performance assessment of PT Angkasa Pura II, through several frameworks, compared to other companies in same industry locally and globally. Then ended by conclusions and recommendation for PT Angkasa Pura II in order to reach a better performance.As a conclusion, PT Angkasa Pura II almost compete the global competition even been a leader in several assessments, with maximum firm value of IDR 11,304,648,783,186.Keywords: airport area economic development, financial statements analysis, airport industry, passenger movement.